2012
DOI: 10.1890/11-1446.1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive geographical clines in the growth and defense of a native plant

Abstract: Broad‐scale geographical gradients in the abiotic environment and interspecific interactions should select for clinal adaptation. How trait clines evolve has recently received increased attention because of anticipated climate change and the importance of rapid evolution in invasive species. This issue is particularly relevant for clines in growth and defense of plants, because both sets of traits are closely tied to fitness and because such sessile organisms experience strong local selection. Yet despite wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
252
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(272 citation statements)
references
References 110 publications
16
252
1
Order By: Relevance
“…Analyses were conducted on log xþ1 values and included treatment as a blocking factor in the statistical model. v www.esajournals.org grown in a common environment, we also found no evidence for correlated expression of latex and cardenolides (n ¼ 22 population means, r ¼ 0.151, p ¼ 0.504; data from Woods et al 2012). This finding is consistent with Koricheva et al's (2004) analysis, which reported very little evidence for trade-offs between defense traits in plants.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Analyses were conducted on log xþ1 values and included treatment as a blocking factor in the statistical model. v www.esajournals.org grown in a common environment, we also found no evidence for correlated expression of latex and cardenolides (n ¼ 22 population means, r ¼ 0.151, p ¼ 0.504; data from Woods et al 2012). This finding is consistent with Koricheva et al's (2004) analysis, which reported very little evidence for trade-offs between defense traits in plants.…”
Section: Resultsmentioning
confidence: 52%
“…An additional population level analysis was conducted based on cardenolide and latex data in Woods et al (2012), which represents 22 populations of A. syriaca across the entire latitudinal range (11 degrees of latitude, from New Brunswick, Canada, to North Carolina, USA). Approximately five individuals of each population were grown in a field common garden in Ithaca, NY, USA and mean population values for cardenolides and latex exudation from the second year of growth were correlated here.…”
Section: Methodsmentioning
confidence: 99%
“…Etterson 2004;Maron et al 2004;Uribe-Salas et al 2008;Bresson et al 2011;Montesinos-Navarro et al 2011;Chen et al 2012;Woods et al 2012). Reciprocal transplant and common garden experiments have been used to determine the degree of plastic versus heritable variation in clinal traits.…”
Section: Space-for-time Substitutions Environmental Gradients and Phmentioning
confidence: 99%
“…Adaptation to local environmental conditions is common among plant species that occur across large environmental gradients (e.g., Pennings et al 2003;Woods et al 2012;Pratt and Mooney 2013;Vergeer and Kunin 2013). Local adaptation can improve plant fitness by affecting traits such as phenology, reproduction and growth, ensuring, for example, that plants flower at a time during which the environment Abstract Species that occur along broad environmental gradients often vary in phenotypic traits that make them better adapted to local conditions.…”
Section: Introductionmentioning
confidence: 99%
“…is most favorable for successful pollination (Linhart and Grant 1996;Woods et al 2012). Because adaptive variation along environmental gradients affects so many aspects of plant fitness, it is also likely to affect interactions among plants.…”
Section: Introductionmentioning
confidence: 99%